The Effects Of Moringa Oleifera Leave Extract On Cytotoxicity And Apoptosis Pathway In Breast Cancer Cell (MCF-7) - Fisall, Umiey Fahietah Mohd (2019)
Moringa oleifera (MO) is belonging to Moringaceae family. In Malaysia, MO was known as „Munggai‟ or „Kelor‟ tree. MO is well known for its therapeutic properties that possesses a wide range of biological activities such as antioxidant and anticancer properties. The impact of different solvents of various degree of polarities on the cytotoxicity of breast cancer cell line (MCF-7), were studied. The cytotoxicity effect of 80 % methanol and its solvent fractions of Moringa oleifera leave (MOL) extract against MCF-7 cell were determined by using MTS assay. The normal breast cell line (MCF-10A) was used to compare with MCF-7 cell. The effective extract that gave the most cytotoxic effect on MCF-7 cell had been chosen. Among of all extracts, dichloromethane extract (DF-CME-MOL) had been selected accordingly to its lowest IC50 (5 μg/mL) and highest selectivity index (SI) (9.5). Then, the chosen extract (DF-CME-MOL) was proceed for further analysis. The phytochemical analysis was performed using DPPH, ABTS, Folin-Ciocalteu, aluminium chloride and GC-MS analysis. An antioxidant contents in DF-CME-MOL for DPPH and ABTS assay were 10.52±0.009 mg/g TEAC and 4.32±0.021 mg/g TEAC, respectively. While, total phenolic and flavonoid content were 34.96±0.006 mg/g GAE and 15.72±0.050 mg/g QUE, respectively. After that, compound analysis by GC-MS detected some potential compounds in DF-CME-MOL named; Phenol, 4-(methoxymethyl)-, 2-Methoxy-4-vinylphenol, Phenol, 2-propyl, Phenol, 2-methoxy-4-(1-propenyl)-, (Z)-, 4-((1E)-3-Hydroxy-1-propenyl)-2-methoxyphenol, Hexadecanoid acid, methyl ester, Phenol, 2-[(4-hydroxyphenyl) methyl], Phenol, 4, 4‟-methylenebis-, Phenol, 2-ethyl-, Benzeneethanol, 4-hydroxy-, Benzaldehyde, 4-hydroxy-, Benzeneacetonitrile, 4-hydroxy- and Benzaldehyde, 3,4-dimethoxy-. Then, apoptosis analysis was carried out by using Annexin V-FITC through flow cytometry FACS and further confirm by Western blot in detected the signalling of apoptosis pathway using selected proteins such as p53, Bax, Cytochrome c and Caspase 8. The DF-CME-MOL greatly induced early apoptosis through extrinsic pathway in MCF-7 cells. Thus, MOL has a potential to be developed into anticancer agent on breast cancer.